OBSTRUCTION ZONE MODELING AT HALIM PERDANAKUSUMA AIRPORT USING REMOTE SENSING DATA - Asep Adang Supriyadi (Ikatan Geografi Indonesia, 2023)
Flight safety plays a critical role in both the national economy and military defense. According to the National Transportation Safety Board (NTSB), the highest number of aircraft accidents between 2013 and 2018 occurred during takeoff (24%) and landing (40%). To model the obstruction zone based on building density and its impact on flight safety, this study utilizes remote sensing data from Sentinel 2A in 2022. The data is analyzed using the Normalized Difference Built-up Index (NDBI) algorithm, which serves as the basis for modeling potential aircraft accident zones. Specifically, the study focuses on the growth of buildings within a 15 km extended runway area during takeoff and landing. The findings reveal that the aircraft takeoff approach area in the Flight Operation Safety Zone (KKOP) at Halim Perdanakusuma Airport exhibits the highest building density. This area demonstrates a moderate level of building density, with a prevailing growth pattern and density that extend predominantly eastward, toward Bekasi city. Furthermore, the study highlights that nearly the entire region falls under the classification of